Improving population policy in Tanzania - Maro, Ichikaeli (1999)
Ichikaeli Maro on behalf of TAMWA reports on the mixed use of family planning services in three areas of Tanzania. The conclusion is that more participatory policy is required to involve women, and also men, in making healthy life choices. - Reproduced
Keywords: Population policy - Tanzania; Population policy